Genetic evaluation of growth rate and efficiency-related traits in Dorper sheep - Yeshaw, Shanbel; Goshme, Shenkute; Abebe, Aschalew; Bisrat, Asfaw; Abebe, Ayele; Zewdie, Tesfaye; Areaya, Alemnew; Mekonnen, Tefera; Eshete, Mesfin; Getachew, Tesfaye (Elsevier, 2023)
The present study was carried out to estimate genetic and phenotypic parameters for growth rate and efficiency-related traits in Dorper sheep. Growth records from the breeding flock of Dorper sheep collected between 2012 and 2021 at Debre Birhan Agricultural Research Center, Amhara Region, Ethiopia were used in this study. (Co)variance components and corresponding genetic parameters for daily gain from birth to weaning (DG0-3), daily gain from weaning to six months (DG3-6), and daily gain from six months to yearling (DG6-12) and corresponding kleiber ratios (KR0-3, KR3-6, KR6-12), efficiency of growth (GE0-3, GE3-6, GE6-12) and relative growth rate (RG0-3, RG3-6, RG6-12) were estimated using restricted maximum likelihood (REML) procedure fitting six different univariate animal models. The most appropriate model for each trait was determined by log-likelihood ratio test. Multivariate analysis was carried out to estimate correlations between traits. Year of birth had a significant effect (P < 0.001) in all studied traits. Furthermore birth season had a significant effect (P < 0.01) in traits measured during pre-weaning growth period. Phenotypic performance for all studied traits except traits measured from six months to 12 months of age showed a declined trend over years. Model including only direct genetic effects was chosen as the most appropriate model for all studied traits, except for GE0-3 and GR0-3 which model included maternal genetic effects was the most appropriate model. Direct heritability estimates were, respectively, 0.10 ± 0.06, 0.16 ± 0.07, 0.26 ± 0.13 and 0.26 ± 0.13 for DG0-3, KR0-3, GE0-3 and GR0-3; 0.02 ± 0.05, 0.02 ± 0.04, 0.00 ± 0.04 and 0.03 ± 0.05 for DG3-6, KR3-6, GE3-6 and GR3-6; and 0.22 ± 0.10, 0.14 ± 0.09, 0.11 ± 0.09 and 0.12 ± 0.09 for DG6-12, KR6-12, GE6-12 and GR6-12. Estimates of the additive genetic coefficients of variation (CVA) were used as a measurement of genetic variability and ranged between 0.78% (GE3-6) and 27.13% (DG6-12). Genetic correlations among the traits ranged from −0.56 (DG3-6 and GE6-12) to 0.99 (KR3-6-GR3-6, GE3-6-GR3-6, GE6-12-GR6-12) and phenotypic correlation ranged from −0.61 (GE6-12-DG3-6) to 0.99 (GR3-6-KR3-6, GR3-6-GE3-6, GR6-12-GE6-12). Traits measured during the pre-weaning growth period had negative and weak genetic correlations with traits measured during the post-weaning growth period and ranged from −0.31 (DG0-3-GE6-12) to 0.20 (DG0-3-DG3-6). The importance of efficiency-related traits will increase significantly and will attract much more attention in sheep production in the central highlands of Ethiopia. Including DG0-3 in the selection index is recommended to improve efficiency of the ongoing Dorper breeding program.